Masticatory Area Influence on Stress in Saddle in Attachments Implant Supported Dentures - ANDREI, OANA CELLA; TIEREAN, MIRCEA HORIA; BURLIBAŞA, MIHAI; DĂGUCI, LUMINIŢA; SCRIECIU, MONICA; FARCAŞIU, CĂTĂLINA; BISOC, ADRIANA; IONESCU, ILEANA; DĂGUCI, CONSTANTIN; TĂNĂSESCU, LIVIA ALICE (University of Bucharest (Bucharest University Press), 2019)
The aim of study was to analyze if placing the second molar influences the maximum von Mises stresses on the saddle and artificial teeth of an implant supported removable partial denture (RPD) with ball attachments. Finite element analysis was used to study stress distribution of a mandibular class I Kennedy RPD with ball attachments and two distal implants, placed bilaterally in the second molar area, in two cases: with or without M2. The value of von Mises stresses was higher in all acrylic components in implant supported RPDs with ball attachments with M2 than the ones in implant supported RPDs with ball attachments without M2. From all acrylic components, the highest von Mises stresses were recorded on M1 in both cases. In metallic saddle, von Mises stresses were higher in RPD without M2 than in RPD with M2. Placing the second artificial molar on the saddle in implant supported RPD with attachments increases the maximum von Mises stresses recorded in the artificial teeth and in the acrylic saddle but lowers them in the metallic component of the saddle. The maximum von Mises stresses recorded in the acrylic saddle are much higher if the second molar is present.
Keywords: Removable partial denture; attachments; implants; saddle; finite elements analysis